Integration of remote sensing-GIS techniques for mapping and monitoring seagrass and ocean colour off Malaysian coasts - Mazlan Hashim, 1961-; Adeli Abdullah, 1964-2002; Abd. Wahid Rasib; Seminar Penyelidikan Dalam Bidang Elektrik, Elektronik, Aeroangkasa, Teknologi Maklumat & Telekomunikasi (1998 : Universiti Teknologi Malaysia, Skudai)
01